The spatial distribution of Aedes aegypti and Aedes albopictus in a transition zone, Rio de Janeiro, Brazil - Rocha, Nildimar Honorio (2009)
Special thanks go to Ary Carvalho de Miranda and Leandro Borges de Miranda for providing logistical support that made this study possible. We thank Marcelo Quintela, Kleber Soares, Olivio F. Souza, Sandro Peixoto and Cristiano Generoso for logistical support in the field, and Manuel Luiz Campos de Souza for providing data on the human population at Oswaldo Cruz Foundation (FIOCRUZ) campus. We thank R. Lourenço-de-Oliveira, M. G. Rosa-Freitas, C. T. Codeço and S. A. Juliano for helpful comments on an earlier version of this manuscript. This work was supported by FIOCRUZ and the Diretoria de Administração do Campus at FIOCRUZ (DIRAC).